Photoplethysmography analysis tool with heart rate variability through poincare and sequence bandwidth assessment - Lim, Si Zhou (Nanyang Technological University, 2022)
As the number of people affected by cardiovascular diseases (CVD) increases each year with hypertension, maintaining of blood pressure levels becomes crucial. Traditionally, it was done using sphygmomanometer which is the clinical standard for measurement. However, the method has proven to be impractical due to the lack of constant monitoring and convenience. Many researchers have thus investigated Photoplethysmography (PPG) wearable technologies in search for a better alternative. The wearables that are currently available such as smartwatches have demonstrated to be relatively inaccurate with motion and noise artifacts and they are not suitable for the adoption in healthcare applications with the lack of clinical information. Hence, there is significant need to develop a technique for obtaining accurate and useful clinical information from PPG.